Sexual healing : the completest guide to overcoming common sexual problems - Keesling, Barbara (Hunter House, 2006)
"A guide to every known sexual problem and all possible treatments, both new and experimental, with over 125 exercises to heal specific problems as well as maintain an intimate bond in relationships"--Provided by publisher.